Change in weight status from childhood to early adulthood and late adulthood risk of colon cancer in men: a population-based cohort study. Issue 10 (October 2018) - Jensen, Britt; Bjerregaard, Lise; Ängquist, Lars; Gögenur, Ismail; Renehan, Andrew; Osler, Merete; Sørensen, Thorkild; Baker, Jennifer
Abstract Background Although weight gain in mid- to late adult life is associated with an increased risk of colon cancer, it is unclear if increases or losses in weight from childhood to early adulthood are differentially associated with risks of adult colon cancer. Methods Weight and height were measured at 7 or 13 years and in early adulthood (17–26 years) in 64, 675 boys in the Copenhagen School Health Records Register and the Danish Conscription Database. Cases of colon cancer (n = 751) were identified in the Danish Cancer Registry. Boys and young men were categorized as normal weight or overweight. Associations between changes in weight and colon cancer were examined using Cox proportional hazards regression to estimate hazard ratios (HRs) and 95% confidence intervals (CIs). Results Compared with men with a normal weight at 7 years and in early adulthood, men with overweight at both ages had an increased risk of adult colon cancer (HR: 2.73, 95% CI 1.80–4.15). In contrast, men with overweight at 7 years, but not in early adulthood did not have an increased risk of colon cancer (HR: 0.73, 95% CI 0.35–1.54), nor did men with a normal weight at 7 years and overweight in early adulthood (HR: 1.28, 95% CI 0.96–1.70). Similar results were observed for weight status at age 13 years combined with early adulthood. Conclusions Childhood overweight that persists into early adulthood is associated with an increased risk of colon cancer, whereas overweight that disappears before early adulthood or developed after childhood is not.